Alexis cool as a cupcake - Simon, Coco (Simon, Coco. Cupcake diaries, 2012)
"Alexis is the clear leader of the Cupcake Club: She's organized, punctual, and happy to take on the stuff like scheduling, budgets, invoicing, and the things that the other girls don't really want to do. In other words, the "unfun" things. But one day Alexis feels particularly unappreciated and informs the Cupcake Club that she is no longer in charge! After deadlines get missed and supplies aren't bought, the girls realize they definitely need a leader. And Alexis realizes being the leader is kind of cool; as long as you know how to ask for help when you need it!"--Information from publisher.